PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) PADA RHJFOX SEBAGAI FORUM DISKUSI - Dewi Immaniar Desrianti; Lusyani Sunarya; Dwi Fitri Parmania (Universitas Raharja, 2015)
The sophistication of information and communication technology (ICT) especially in the field of internet is very supportive and easier to find information by using a web browser as a medium, one of the utilization of information and communication technology (ICT) is an online discussion forum as access to discuss various things. Discussion forums active role as a communication medium that exists with the purpose of giving opinions, motivation, solutions, and information related to the ongoing discussion in the forum. Along with the development of non-formal learning methods, discussion forums are now made by several campuses in Indonesia, which aims to provide solutions to the students to be more active in asking and able to provide accurate answers or opinions thus indirectly the discussion forum turned into a place of learning non- formal distance can be done without face to face (ilearning learning methods). The problem is access to the previous discussion forum where discussions are time limitations in the delivery time, require each member to take the time to meet face to face and also requires that each member be in one (1) point for the purpose of exchanging information. Online discussion forums is an efficient solution is flexible and does not remember much each member has the same time, by making use of information and communication technology (ICT) is one of the colleges make online discussion forums as a forum of discussion among students, faculty and staff at the college incorporated as members so that the members can ask questions and provide solutions, and argue about related questions to give you an idea - an idea that is easy to understand that is packaged specifically for non-learning activities fomal online and without a time bound access. RhjFox is a communication medium in the form of active online discussion forum developed by the university, with a discussion of the division of the categories created to facilitate the members to interact and search for information on the desired topic of discussion in the discussion forum. RhjFox is a contribution to improving the quality of interaction and discussion without the limitations of time and face to face which involves students, faculty and staff members who had previously performed only discussion forum at the time and the same place